Microstructure and mechanical properties as a function of process parameters for Ti6Al4V produced by high power laser powder bed fusion - Pistorius, P.G.H. (Pieter) (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2019.